Effects of contracting out and reduction in force of federal employees : (Kodiak, Alaska) : hearing before the Subcommittee on Human Resources of the Committee on Post Office and Civil Service, House of Representatives, One Hundred First Congress, first session, August 17, 1989. - United States. Congress. House. Committee on Post Office and Civil Service. Subcommittee on Human Resources. (Washington : U.S. G.P.O. : For sale by the Supt. of Docs., Congressional Sales Office, U.S. G.P.O., 1990)
Item 1022-B, 1022-C (MF). "Serial no. 101-76." Shipping list no.: 91-039-P. Distributed to some depository libraries in microfiche. Mode of access: Internet.